Kontribusi Bani Asakir Pada Masa Keemasan Islam di Damaskus - ilham wahyudi; -, Rustam; Roza, Ellya (Nazharat: Jurnal Kebudayaan, 2024)
This research aims to explore the contribution of the Banu Asakir during the golden age of Islam in Damascus. With a qualitative historical approach, this study examines the role of Bani Asakir in political, economic, and cultural aspects that affect the development of the city of Damascus. Data was obtained through the analysis of historical texts, archival documents, and relevant literature. This study examines the contribution of the Banu Asakir during the golden age of Islam in Damascus, which lasted from the 7th to the 13th centuries AD. The Bani Asakir, as one of the leading families, played a significant role in the political, economic, and cultural aspects that influenced the development of society in this city. In the political sphere, they function as advisors and mediators, helping to maintain the stability of the government. Economically, the Banu Asakir established trade and industrial ventures that strengthened Damascus' position as a center of international trade. In the cultural aspect, they supported science and the arts, making Damascus an important center of Islamic culture. This research shows that Bani Asakir's contribution is not only focused on power, but also includes efforts to advance society as a whole.